2018
DOI: 10.1186/s12959-018-0161-9
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic events in cancer patients on active treatment with cisplatin-based chemotherapy: another look!

Abstract: BackgroundThe risk of thromboembolic events is higher among cancer patients, especially in patients undergoing chemotherapy. Cisplatin-based regimens claim to be associated with a very high thromboembolic rate. In this study, we report on our own experience with thrombosis among patients on active cisplatin-based chemotherapy.MethodsMedical records and hospital databases were searched for all the patients treated with any cisplatin-based regimen for any kind of cancer. Thrombosis was considered cisplatin-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
1
35
0
1
Order By: Relevance
“…Among the whole group, thromboembolic events were confirmed in 6.6% but was highest (20.9%) in patients with gastric cancer. In multivariate analysis, significantly higher rates of thrombosis were associated with gastric, as the primary tumor, and advanced-stage disease 19 . More recently, the FLOT4 (fluorouracil plus leucovorin, oxaliplatin and docetaxel) trial also showed lower risk of thromboembolic events in the cisplatin-free regimen (FLOT4) compared to other cisplatin-containing regimens 20 .…”
Section: Discussionmentioning
confidence: 94%
“…Among the whole group, thromboembolic events were confirmed in 6.6% but was highest (20.9%) in patients with gastric cancer. In multivariate analysis, significantly higher rates of thrombosis were associated with gastric, as the primary tumor, and advanced-stage disease 19 . More recently, the FLOT4 (fluorouracil plus leucovorin, oxaliplatin and docetaxel) trial also showed lower risk of thromboembolic events in the cisplatin-free regimen (FLOT4) compared to other cisplatin-containing regimens 20 .…”
Section: Discussionmentioning
confidence: 94%
“…The platinum compounds such as cisplatin are alkyl-like agents that are associated with Raynaud phenomenon, hypertension, MI, stroke, arterial thrombosis, acute limb ischemia, deep vein thrombosis (DVT), and pulmonary embolism. 3134 Furthermore, chest pain has been reported in as many as 38% of patients with testicular cancer treated with cisplatin in combination with vinca alkaloids and bleomycin. 25 These adverse events are likely the result of direct toxic effects on endothelial cells, platelet activation, and decreased nitric oxide availability.…”
Section: Vascular Complications Of Traditional Therapiesmentioning
confidence: 99%
“…The Khorana score is a predictive model for chemotherapy-associated TEE and is based on the following: (1) Site of cancer; (2) Prechemotherapy platelet count 350 × 10 9 /L or more; (3) Hemoglobin level less than 100 g/L or use of red cell growth factors; (4) Prechemotherapy leukocyte count more than 11 × 10 9 /L; and (5) BMI 35 kg/m 2 or more[ 2 , 20 , 21 ]. The risk of TEE is 4-6-fold higher in patients with cancer than in those without, and the TEE incidence is 3%-15% annually in cancer patients[ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the American Cancer Society, approximately 9610 new cases of testicular cancer will be diagnosed in 2020 with 440 deaths[ 1 ]. One in every 250 males will develop testicular cancer during their lifetime[ 1 , 2 ]. With the emergence of cisplatin-based chemotherapy in the 1970’s[ 3 ], patients with testicular cancer are able to attain a 5-year survival rate of more than 95%[ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%